2011
DOI: 10.1111/j.1440-1746.2010.06605.x
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism at exon 7 splice acceptor site of OAS1 gene determines response of hepatitis C virus patients to interferon therapy

Abstract: This is the first study to show a significant association between the functional SNP at exon 7 SAS of OAS1 gene and the viral response to interferon in chronic HCV patients. Patients with AA genotype were associated with progressive HCV disease and viral resistance to interferon therapy. This OAS SNP is a potential bio-marker to predict IFN response in chronic hepatitis C patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…The Neandertal-introgressed allele encodes a protein variant (p46) that is associated with higher enzymatic activity [36]. The adaptive potential of this variant is supported by the observation that this variant (or other variants in strong LD with it) was shown to be associated with: (1) reduced infection and replication rates of West Nile virus ([38], but see [39]); (2) improved resistance to hepatitis C virus (HCV) infection [40, 41]; and (3) variable symptomology of tick-borne encephalitis (TBE) virus-induced disease (homozygous individuals for the Neandertal haplotype show the most severe symptoms of TBE). Strikingly, West Nile, hepatitis C, and TBE are all members of the Flaviviridae family, suggesting that Flaviviruses might have been the main drivers of selection in OAS1 .…”
Section: Discussionmentioning
confidence: 99%
“…The Neandertal-introgressed allele encodes a protein variant (p46) that is associated with higher enzymatic activity [36]. The adaptive potential of this variant is supported by the observation that this variant (or other variants in strong LD with it) was shown to be associated with: (1) reduced infection and replication rates of West Nile virus ([38], but see [39]); (2) improved resistance to hepatitis C virus (HCV) infection [40, 41]; and (3) variable symptomology of tick-borne encephalitis (TBE) virus-induced disease (homozygous individuals for the Neandertal haplotype show the most severe symptoms of TBE). Strikingly, West Nile, hepatitis C, and TBE are all members of the Flaviviridae family, suggesting that Flaviviruses might have been the main drivers of selection in OAS1 .…”
Section: Discussionmentioning
confidence: 99%
“…The G allele is known to be associated with higher enzyme activity, whereas the more common A allele is associated with lower enzyme activity [26]. It is particularly noteworthy that patients with the homozygous GG genotype demonstrated a higher response to interferon therapy against HCV infection, whereas the AA genotype was associated with non-response to interferon and higher degrees of liver fibrosis [27]. We found by genomic sequence analysis that Huh7 cell line possesses the AA genotype and confirmed by RT-PCR the expression of the splicing variants coding for p42, p48 and p52, respectively, but no expression of p46 transcript (Supplementary data Fig.…”
Section: The Antiviral Activity Of Oas1 P46 Against Hcvmentioning
confidence: 99%
“…Consistent with the important role of OAS proteins in viral infection, it was shown that polymorphisms in the OAS genes are associated with increased susceptibility to HCV infection[18] and IFN treatment outcomes[17,19,20]. However, the molecular basis for this association is not well understood.…”
Section: Discussionmentioning
confidence: 99%